GluN2A/ERK/CREB Signaling Pathway Involved in Electroacupuncture Regulating Hypothalamic-Pituitary-Adrenal Axis Hyperactivity - Wang, Yu; Han, Jing; Zhu, Jing; Zhang, Mizhen; Ju, Minda; Du, Yueshan; Tian, Zhanzhuang (Frontiers in Neuroscience, 2021)
The hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis caused by stress will inevitably disrupt the homeostasis of the neuroendocrine system and damage physiological functions. It has been demonstrated that electroacupuncture (EA) can modulate HPA axis hyperactivity during the perioperative period. As the initiating factor of the HPA axis, hypothalamic corticotrophin-releasing hormone (CRH) is the critical molecule affected by EA. However, the mechanism by which EA reduces CRH synthesis and secretion remains unclear. Activated N-methyl-D-aspartate receptor (NMDAR) has been linked to over-secretion of hypothalamic CRH induced by stress. To determine whether NMDAR is involved in EA regulating the over-expression of CRH, a surgical model of partial hepatectomy (HT) was established in our experiment. The effect of EA on hypothalamic NMDAR expression in HT mice was examined. Then, we investigated whether the extracellular regulated protein kinases (ERK)/cyclic adenosine monophosphate response element-binding protein (CREB) signaling pathway mediated by NMDAR was involved in EA regulating HPA axis hyperactivity. It was found that surgery enhanced the expression of hypothalamic CRH and caused HPA axis hyperactivity. Intriguingly, EA effectively suppressed the expression of CRH and decreased hyperphosphorylation of NR2A, ERK, and CREB in HT mice. Both NR2A and CREB antagonists had similar effects on normalizing the expression of CRH and HPA axis function compared with EA. Our findings suggested that surgery enhanced the phosphorylation of the hypothalamic NR2A/ERK/CREB signaling pathway, thus promoting the synthesis and secretion of CRH. EA suppressed the phosphorylation of NR2A, ERK, and CREB in mice that had undergone surgery, indicating that the NR2A/ERK/CREB signaling pathway was involved in EA alleviating HPA axis hyperactivity.